Macrophage Activation Assays to Evaluate the Immunostimulatory Capacity of Avibacterium paragallinarum in A Multivalent Poultry Vaccine - van den Biggelaar, Robin H. G. A. (Vaccines (Basel), 2020)
High-quality vaccines are crucial to prevent infectious disease outbreaks in the poultry industry. In vivo vaccination tests are routinely used to test poultry vaccines for their potency, i.e., their capacity to induce protection against the targeted diseases. A better understanding of how poultry vaccines activate immune cells will facilitate the replacement of in vivo potency tests for in vitro assays. Using the chicken macrophage-like HD11 cell line as a model to evaluate innate immune responses, the current explorative study addresses the immunostimulatory capacity of an inactivated multivalent vaccine for infectious bronchitis, Newcastle disease, egg-drop syndrome, and infectious coryza. The vaccine stimulated HD11 cells to produce nitric oxide and to express pro-inflammatory cytokines IL-1β, TNF, and IL-12p40, chemokines CXCLi1 and CXCLi2, and the anti-inflammatory cytokine IL-10, but only when inactivated Avibacterium paragallinarum, the causative agent of infectious coryza, was present. Lipopolysaccharides from Avibacterium paragallinarum were crucial for the production of nitric oxide and expression of IL-1β and CXCLi1. The described immune parameters demonstrate the capacity of this multivalent vaccine to activate innate immune cells and may in the future, combined with antigen quantification methods, contribute to vaccine quality testing in vitro, hence the replacement of current in vivo vaccination tests.